Technologies and systems to improve mobility of visually impaired people : a state of the art - Paiva, Sara (2022)
The concept of mobility is an important aspect for citizens and, given the development of cities, is gaining more and more importance each day. Although it is possible to speak of mobility solutions for the general citizen, there are very specific characteristics such as visually impaired people, which require specific and different solutions. In this chapter, we review the literature regarding solutions and technologies that are being used to assist in the mobility of visually impaired people, both in indoor and outdoor environments, as well as in the detection of obstacles, which may occur in both types of environment. We present some recent research in these three main categories and also present a discussion and summary of main technologies, approaches, and equipment used.